Sub-Nanomolar Sensitivity of Nitric Oxide Mediated Regulation of cGMP and Vasomotor Reactivity in Vascular Smooth Muscle - Held, Kara F.; Dostmann, Wolfgang R. (Frontiers in Pharmacology, 2012)
Nitric oxide (NO) is a potent dilator of vascular smooth muscle (VSM) by modulating intracellular cGMP ([cGMP]i) through the binding and activation of receptor guanylyl cylases (sGC). The kinetic relationship of NO and sGC, as well as the subsequent regulation of [cGMP]i and its effects on blood vessel vasodilation, is largely unknown. In isolated VSM cells exposed to both pulsed and clamped NO we observed transient and sustained increases in [cGMP]i, with subnanomolar sensitivity to NO (EC50=0.28nM). Through the use of pharmacological inhibitors of sGC, PDE5 and PKG, a comprehensive VSM-specific modeling algorithm was constructed to elucidate the concerted activity profiles of sGC, PDE5, phosphorylated-PDE5, and PDE1 in the maintenance of [cGMP]i. In small pressure-constricted arteries of the resistance vasculature we again observed both transient and sustained relaxations upon delivery of pulsed and clamped NO, while maintaining a similarly high sensitivity to NO (EC50=0.42nM). Our results propose an intricate dependency of the messengers and enzymes involved in cGMP homeostasis, and vasodilation in VSM. Particularly, the high sensitivity of sGC to NO in primary tissue indicates how small changes in the concentrations of NO, irrespective of the form of NO delivery, can have significant effects on the dynamic regulation of vascular tone.